A Comparison of Different Operating Systems for Femtosecond Lasers in Cataract Surgery - B. M. Wu; G. P. Williams; A. Tan; J. S. Mehta (Journal of Ophthalmology)
The introduction of femtosecond lasers is potentially a major shift in the way we approach cataract surgery. The development of increasingly sophisticated intraocular lenses (IOLs), coupled with heightened patient expectation of high quality postsurgical visual outcomes, has generated the need for a more precise, highly reproducible and standardized method to carry out cataract operations. As femtosecond laser-assisted cataract surgery (FLACS) becomes more commonplace in surgical centers, further evaluation of the potential risks and benefits needs to be established, particularly in the medium/long term effects. Healthcare administrators will also have to weigh and balance out the financial costs of these lasers relative to the advantages they put forth. In this review, we provide an operational overview of three of five femtosecond laser platforms that are currently commercially available: the Catalys (USA), the Victus (USA), and the LDV Z8 (Switzerland).